Ulcerative Necrotic Gingivitis and Modern Treatment Methods - Kurbon, Xudaykulov; Nozima, Ikromova; Adxam, Azimov; Ahmadjon, Ergashev; Munisovna, Xaydarova Durdona (American Journal of Bioscience and Clinical Integrity, 2025)
Acute necrotizing ulcerative gingivitis is a painful infection of the gums. Symptoms include severe pain, bleeding, and bad breath. Diagnosis is based on clinical presentation. Treatment consists of gentle brushing, improved oral hygiene, mouthwash, supportive care, and antibiotics if brushing is delayed.